PELATIHAN SISTEM PENGENDALIAN INTERNAL USAHA MIKRO - Supeni Anggraeni Mapuasari; Mila Austria Reyes; Andrianantenaina Hajanirina; Muhamad Safiq; Liswandi (POLITEKNIK LP3I JAKARTA, 2024)
Understanding accounting system and internal control is part of managerial accounting skill that lead to SME success. As micro business, people often ignore this in the name of small size of gross revenue. In fact, failure to manage simple system such as the separated entity principles will lead to internal control failure. It is often correlated with financial management failure and many times creates bankruptcy. This training is specially purposed for assisting micro business owner to understand basic principles of internal control and accounting system. This activity was done in Bekasi, taken place at Bale Bamboo Resto, December 22, 2022. Thirty two micro business owners were attending the workshop. Utilizing several simple software available free in the play store, the micro business owner can implements several control principles.